Historisitas Pemikiran Hukum Imam Asy-Syafi'i - Rohidin Rohidin (Jurnal Hukum IUS QUIA IUSTUM, 2004)
Ass-Syafi'i, is well known as a "mejtahid" who developed the "qodim"and" jaidi"schools of thought which emerged after along period of study in various legal centres araound the world. The result of these in-depth studies of various methods of schools of thought was an effort in synthesis. This environmen the experienced made a signiticant contribution to the development of his legal thought. Not limited to this, heals of felt that he should off era method ofthrought that was systematic, thought the logic of fikih.